Weather-resistant nano elastic paint and preparation method thereof

By covering nano-scale titanium dioxide on the surface of the glass flakes and combining nano-titanium dioxide, the shortcomings of nano-coatings in terms of weather resistance are solved, and the weather resistance and corrosion resistance of the coating are significantly improved, forming an excellent protective barrier.

CN119307157AActive Publication Date: 2025-01-14ANHUI KAILIN ADVANCED MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411663872.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Existing nanocoatings have shortcomings in weather resistance, especially the ultraviolet resistance of glass flakes is relatively average, which affects the overall performance of the coating.

Method used

The surface of the glass flakes is coated with nanoscale titanium dioxide, and combined with the additional nanotitanium dioxide, the coating's UV resistance and corrosion resistance are improved through modification treatment.

Benefits of technology

The weather resistance and corrosion resistance of the coating are significantly improved. Through the barrier effect of modified glass flakes and the filling of nanotitanium dioxide, an excellent protective barrier is formed, which reduces the damage to the coating by ultraviolet rays and improves the overall performance of the coating. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144127310000071
    Figure BDA0005144127310000071
  • Figure BDA0005144127310000082
    Figure BDA0005144127310000082
Patent Text Reader

Abstract

The invention relates to the technical field of nano elastic paint, in particular to weather-resistant nano elastic paint and a preparation method thereof.The preparation method comprises the steps that epoxy resin, modified glass flakes, nano titanium dioxide and an organic solvent are put into a high-speed dispersion machine and stirred to be uniform, and a mixture is obtained; and putting the curing agent into the high-speed dispersion machine, and continuously stirring to obtain the weather-resistant nano elastic paint. According to the elastic paint disclosed by the invention, the surface of the glass flake is coated with the nano-scale titanium dioxide, and the nano-scale titanium dioxide is matched with the additionally added nano-scale titanium dioxide for common use, so that the overall performance of the elastic paint is improved; specifically, the coated nano-scale titanium dioxide improves the ultraviolet light resistance of the glass flake, can well reduce the damage of ultraviolet light to the coating, and improves the weather resistance; moreover, the modified glass flakes are mutually overlapped in the coating matrix to form a barrier, and the nano titanium dioxide can be filled in gaps which are not fully overlapped, so that the coating has excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano elastic paint, in particular to a weather-resistant nano elastic paint and a preparation method thereof. Background Art

[0002] Nano coatings are a kind of protective material widely used in modern industrial industries. They have achieved good applications in many aspects such as concrete facility base protection, metal material surface treatment protection, and construction equipment protection. Using the small size effect, surface and interface effect, and quantum size effect of nanoparticles, applying nanotechnology to the coating synthesis process, and preparing nano functional coatings has become an important development direction of modern coating research.

[0003] By adding glass flakes to the coating matrix, after forming the coating, the glass flakes in it are arranged layer by layer to form a good sealing barrier, which improves the corrosion resistance of the coating; even if some coatings will improve the weather resistance by adding additional nanofillers, the glass flakes themselves have a relatively general anti-ultraviolet performance, which affects the weather resistance of the final coating. Based on this, a weather-resistant nano elastic paint and a preparation method thereof are proposed. Summary of the invention

[0004] In order to address the deficiencies of the prior art, the present invention provides a weather-resistant nano elastic paint and a preparation method thereof, which improves the overall performance of the elastic paint by coating nano-grade titanium dioxide on the surface of glass flakes and using it in combination with additionally added nano-titanium dioxide.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a weather-resistant nano elastic paint, comprising the following raw materials in parts by weight: 40-50 parts of epoxy resin, 20-25 parts of modified glass flakes, 10-15 parts of nano titanium dioxide, 5-10 parts of curing agent, and 5-10 parts of organic solvent.

[0006] Preferably, the preparation of modified glass flakes and nano-titanium dioxide is as follows: S1. Glass microflakes with a diameter of more than 3 mm are placed in a saturated solution of calcium hydroxide for treatment. After the treatment is completed, the glass microflakes are filtered and dried to obtain pretreated glass microflakes; S2. The pretreated glass microflakes are dispersed in deionized water, and the pH value is adjusted to 2-4 with hydrochloric acid. The system temperature is controlled to 65-75°C, and then a titanium tetrachloride ethanol solution prepared from titanium tetrachloride and anhydrous ethanol is added dropwise. After the reaction is completed, the filter is filtered to obtain a filtered solid and a filtrate; S3. The filtered solid is rinsed, calcined and then ground to obtain modified glass flakes with a diameter of less than 0.1 mm; S4. Titanium tetrachloride is continued to be added to the filtrate, and after reaction and calcination, nano-titanium dioxide is obtained.

[0007] Preferably, in step S1, the treatment temperature is 80-90° C. and the treatment time is 8-12 h.

[0008] Preferably, in step S2, the concentration of the titanium tetrachloride ethanol solution is 220 g / L; and the reaction time is 1-1.5 h.

[0009] Preferably, in step S2, the molar ratio of the glass microsheets to titanium tetrachloride is 1:(0.1-0.2).

[0010] Preferably, in step S1, the diameter of the glass microsheet is 3-5 mm; in step S3, the diameter of the glass flake is 0.05-0.1 mm.

[0011] Preferably, in step S4, the amount of titanium tetrachloride added is 10-15% of the total mass of the filtrate.

[0012] Preferably, the curing agent is a cashew nut oil modified epoxy curing agent or a polyamide epoxy curing agent.

[0013] Preferably, the organic solvent is any one or more combinations of butanol, toluene and xylene.

[0014] The present invention also provides a method for preparing a weather-resistant nano elastic paint, comprising the following steps:

[0015] (1) putting epoxy resin, modified glass flakes, nano titanium dioxide and organic solvent into a high-speed disperser and stirring them uniformly to obtain a mixture;

[0016] (2) Put the curing agent into a high-speed disperser and continue stirring to obtain a weather-resistant nano elastic paint.

[0017] The present invention provides a weather-resistant nano elastic paint and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0018] The present invention improves the overall performance of the elastic paint by coating nano-scale titanium dioxide on the surface of glass flakes and using them together with additionally added nano-scale titanium dioxide; specifically, the coated nano-scale titanium dioxide improves the ultraviolet light protection ability of the glass flakes, which can effectively reduce the damage of ultraviolet rays to the coating and improve weather resistance; and the modified glass flakes overlap each other in the coating matrix to form a barrier, and the nano-scale titanium dioxide can fill in the gaps that are not fully overlapped, so that the coating has excellent corrosion resistance.

[0019] When coating titanium dioxide, the present invention uses glass microflakes with larger flake diameters to reduce agglomeration, which is beneficial for uniform coating of titanium dioxide on the surface of the microflakes. Then, by grinding, uniformly coated glass flakes can be obtained, thereby further improving the weather resistance of the coating.

[0020] The present invention uses calcium hydroxide solution to pretreat the glass microchips to generate a layer of silicate water compound on the surface thereof, which plays a certain buffering role during calcination, reduces the thermal expansion stress of glass and titanium dioxide, thereby reducing the amount of cracks in the titanium dioxide coating layer and improving the performance of the coating to a certain extent. DETAILED DESCRIPTION

[0021] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0022] Example 1

[0023] The preparation of modified glass flakes and nano-titanium dioxide is as follows:

[0024] S1. Place a glass microchip with a diameter of 3 mm into a saturated calcium hydroxide solution and treat it at 90° C. for 8 h. After the treatment, filter and dry it to obtain a pretreated glass microchip.

[0025] S2. Disperse the pretreated glass microchips in deionized water, adjust the pH value to 4 with hydrochloric acid, control the system temperature to 65°C, and then drop a 220 g / L titanium tetrachloride ethanol solution prepared from titanium tetrachloride and anhydrous ethanol. After reacting for 1.5 hours, filter and obtain a solid filter and a filtrate; wherein the molar ratio of the glass microchips to titanium tetrachloride is 1:0.1.

[0026] S3. The filtered solid is rinsed, calcined and then ground to obtain modified glass flakes with a flake diameter of 0.1 mm.

[0027] S4. Continue to add titanium tetrachloride to the filtrate, the amount of titanium tetrachloride added is 10% of the total mass of the filtrate, and after reaction and calcination, nano titanium dioxide is obtained.

[0028] Example 2

[0029] The preparation of modified glass flakes and nano-titanium dioxide is as follows:

[0030] S1. Place a glass microchip with a diameter of 5 mm into a saturated calcium hydroxide solution and treat it at 80° C. for 12 hours. After the treatment is completed, filter and dry to obtain a pretreated glass microchip.

[0031] S2. Disperse the pretreated glass microchips in deionized water, adjust the pH value to 2 with hydrochloric acid, control the system temperature to 75°C, and then drop a 220 g / L titanium tetrachloride ethanol solution prepared from titanium tetrachloride and anhydrous ethanol. After reacting for 1 hour, filter and obtain a solid and a filtrate; wherein the molar ratio of the glass microchips to titanium tetrachloride is 1:0.2.

[0032] S3. The filtered solid is rinsed, calcined and then ground to obtain modified glass flakes with a flake diameter of 0.05 mm.

[0033] S4. Continue to add titanium tetrachloride to the filtrate, the amount of titanium tetrachloride added is 15% of the total mass of the filtrate, and after reaction and calcination, nano titanium dioxide is obtained.

[0034] Example 3

[0035] The preparation of modified glass flakes and nano-titanium dioxide is as follows:

[0036] S1. Place a glass microchip with a diameter of 4 mm into a saturated calcium hydroxide solution and treat it at 85° C. for 10 h. After the treatment, filter and dry it to obtain a pretreated glass microchip.

[0037] S2. Disperse the pretreated glass microchips in deionized water, adjust the pH value to 3 with hydrochloric acid, control the system temperature to 70°C, and then drop a 220 g / L titanium tetrachloride ethanol solution prepared from titanium tetrachloride and anhydrous ethanol. After reacting for 1.2 hours, filter and obtain a solid filter and a filtrate; wherein the molar ratio of the glass microchips to titanium tetrachloride is 1:0.15.

[0038] S3. The filtered solid is rinsed, calcined and then ground to obtain modified glass flakes with a flake diameter of 0.08 mm.

[0039] S4. Continue to add titanium tetrachloride to the filtrate, the amount of titanium tetrachloride added is 12% of the total mass of the filtrate, and after reaction and calcination, nano titanium dioxide is obtained.

[0040] Example 4

[0041] A weather-resistant nano elastic paint comprises the following raw materials in parts by weight: 50 parts of epoxy resin, 20 parts of modified glass flakes in Example 1, 15 parts of nano titanium dioxide in Example 1, 5 parts of cashew nut oil-modified epoxy curing agent, and 10 parts of toluene.

[0042] The preparation method of the weather-resistant nano elastic paint comprises the following steps:

[0043] (1) putting epoxy resin, modified glass flakes, nano titanium dioxide and toluene into a high-speed disperser and stirring them uniformly to obtain a mixture;

[0044] (2) Put the cashew nut oil modified epoxy curing agent into a high-speed disperser and continue stirring to obtain a weather-resistant nano elastic paint.

[0045] Example 5

[0046] A weather-resistant nano elastic paint comprises the following raw materials in parts by weight: 40 parts of epoxy resin, 25 parts of modified glass flakes in Example 2, 10 parts of nano titanium dioxide in Example 2, 10 parts of polyamide epoxy curing agent, and 5 parts of xylene.

[0047] The preparation method of the weather-resistant nano elastic paint comprises the following steps:

[0048] (1) putting epoxy resin, modified glass flakes, nano titanium dioxide and xylene into a high-speed disperser and stirring them evenly to obtain a mixture;

[0049] (2) Put the polyamide epoxy curing agent into a high-speed disperser and continue stirring to obtain a weather-resistant nano elastic paint.

[0050] Example 6

[0051] A weather-resistant nano elastic paint comprises the following raw materials in parts by weight: 45 parts of epoxy resin, 22 parts of modified glass flakes in Example 3, 12 parts of nano titanium dioxide in Example 3, 8 parts of cashew nut oil-modified epoxy curing agent, and 8 parts of butanol.

[0052] The preparation method of the weather-resistant nano elastic paint comprises the following steps:

[0053] (1) putting epoxy resin, modified glass flakes, nano titanium dioxide and butanol into a high-speed disperser and stirring them evenly to obtain a mixture;

[0054] (2) Put the cashew nut oil modified epoxy curing agent into a high-speed disperser and continue stirring to obtain a weather-resistant nano elastic paint.

[0055] Comparative Example 1

[0056] A weather-resistant nano elastic paint and a preparation method thereof are basically the same as those of Example 6, except that the modified glass flakes are replaced with ordinary glass flakes (with a flake diameter of 0.08 mm).

[0057] Comparative Example 2

[0058] A weather-resistant nano elastic paint and preparation method, which is basically the same as Example 6, except that: the preparation of modified glass flakes and nano titanium dioxide is as follows:

[0059] S1. Place a glass microchip with a diameter of 0.08 mm into a saturated calcium hydroxide solution and treat it at 85° C. for 10 h. After the treatment, filter and dry it to obtain a pretreated glass microchip.

[0060] S2. Disperse the pretreated glass microchips in deionized water, adjust the pH value to 3 with hydrochloric acid, control the system temperature to 70°C, and then drop a 220 g / L titanium tetrachloride ethanol solution prepared from titanium tetrachloride and anhydrous ethanol. After reacting for 1.2 hours, filter and obtain a solid filter and a filtrate; wherein the molar ratio of the glass microchips to titanium tetrachloride is 1:0.15.

[0061] S3. The filtered solid is rinsed, calcined and then ground to obtain modified glass flakes with a flake diameter of 0.08 mm.

[0062] S4. Continue to add titanium tetrachloride to the filtrate, the amount of titanium tetrachloride added is 12% of the total mass of the filtrate, and after reaction and calcination, nano titanium dioxide is obtained.

[0063] Comparative Example 3

[0064] The preparation of modified glass flakes and nano-titanium dioxide is as follows:

[0065] S1. Disperse glass microchips with a diameter of 4 mm in deionized water, adjust the pH to 3 with hydrochloric acid, control the system temperature to 70°C, then drop a 220 g / L titanium tetrachloride ethanol solution prepared from titanium tetrachloride and anhydrous ethanol, and filter after reacting for 1.2 hours to obtain a solid and a filtrate; wherein the molar ratio of the glass microchips to titanium tetrachloride is 1:0.15.

[0066] S2. The filtered solid is rinsed, calcined and then ground to obtain modified glass flakes with a flake diameter of 0.08 mm.

[0067] S3. Continue to add titanium tetrachloride to the filtrate, the amount of titanium tetrachloride added is 12% of the total mass of the filtrate, and after reaction and calcination, nano titanium dioxide is obtained.

[0068] Comparative Example 4

[0069] A weather-resistant nano elastic paint comprises the following raw materials in parts by weight: 45 parts of epoxy resin, 22 parts of modified glass flakes in Example 3, 8 parts of cashew nut oil-modified epoxy curing agent, and 8 parts of butanol.

[0070] The preparation method of the weather-resistant nano elastic paint comprises the following steps:

[0071] (1) putting epoxy resin, modified glass flakes and butanol into a high-speed disperser and stirring them evenly to obtain a mixture;

[0072] (2) Put the cashew nut oil modified epoxy curing agent into a high-speed disperser and continue stirring to obtain a weather-resistant nano elastic paint.

[0073] Quality Inspection

[0074] The weather-resistant nano elastic paint prepared in Examples 4-6 and Comparative Examples 1-4 was sprayed on a sample plate, and the performance was tested after standing at room temperature for 7 days. The specific results are shown in the following table.

[0075] 1. Abrasion resistance: Tested according to GB / T1768-89 Determination of paint film abrasion resistance, load 500g, grinding speed 500r.

[0076] 2. Weather resistance: Use a UV aging test box to test the coating's UV aging weather resistance. Place the coating in a UV aging box with UV radiation (313nm, 1.25kw) and continuously irradiate it. Observe the degree of coating aging at regular intervals.

[0077] 3. Salt spray resistance test: Use a salt spray test chamber to conduct salt spray test on the coating samples.

[0078] Table 1 Wear resistance

[0079]

[0080]

[0081] Table 2 Weather resistance and salt spray resistance

[0082]

[0083] It can be seen from the above table that the coatings in Comparative Examples 1-4 are not as good as those in Example 6 in terms of weather resistance, salt spray resistance and wear resistance, indicating that the use of nano-titanium dioxide coated glass flakes for modification can greatly improve the overall quality of the coating; and first using large-diameter glass microflakes for coating and then refining them into small-diameter glass flakes can reduce the problem of deterioration of the coating effect due to agglomeration, thereby improving the weather resistance of the coating; the use of nano-titanium dioxide and modified glass flakes in combination can make up for the gaps in the modified glass flake laminated barrier in the coating, thereby improving the salt spray resistance of the coating.

[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A weather-resistant nano elastic paint, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of epoxy resin, 20-25 parts of modified glass flakes, 10-15 parts of nano titanium dioxide, 5-10 parts of curing agent and 5-10 parts of organic solvent.

2. The weather-resistant nano elastic paint according to claim 1, characterized in that: The preparation of modified glass flakes and nano-titanium dioxide is as follows: S1, placing glass microchips with a diameter of more than 3 mm into a saturated calcium hydroxide solution for treatment, filtering and drying after the treatment is completed to obtain pretreated glass microchips; S2, dispersing the pretreated glass micro-sheets in deionized water, adjusting the pH thereof to 2-4 with hydrochloric acid, controlling the system temperature to 65-75° C., then dropwise adding a titanium tetrachloride ethanol solution prepared from titanium tetrachloride and anhydrous ethanol, and filtering after the reaction is completed to obtain a filtrate solid and a filtrate; S3, washing the filtered solid, grinding it after calcination, and obtaining modified glass flakes with a flake diameter of less than 0.1 mm; S4. Continue to add titanium tetrachloride to the filtrate, and after reaction and calcination, obtain nano titanium dioxide.

3. The weather-resistant nano elastic paint according to claim 2, characterized in that: In step S1, the treatment temperature is 80-90°C and the treatment time is 8-12h.

4. The weather-resistant nano elastic paint according to claim 2, characterized in that: In step S2, the concentration of the titanium tetrachloride ethanol solution is 220 g / L; and the reaction time is 1-1.5 h.

5. The weather-resistant nano elastic paint according to claim 2, characterized in that: In step S2, the molar ratio of the glass microsheet to titanium tetrachloride is 1:(0.1-0.2).

6. The weather-resistant nano elastic paint according to claim 2, characterized in that: In step S1, the diameter of the glass microsheet is 3-5 mm; in step S3, the diameter of the glass flake is 0.05-0.1 mm.

7. The weather-resistant nano elastic paint according to claim 2, characterized in that: In step S4, the amount of titanium tetrachloride added is 10-15% of the total mass of the filtrate.

8. The weather-resistant nano elastic paint according to claim 1, characterized in that: The curing agent is cashew nut oil modified epoxy curing agent or polyamide epoxy curing agent.

9. The weather-resistant nano elastic paint according to claim 1, characterized in that: The organic solvent is any one or more combinations of butanol, toluene and xylene.

10. The method for preparing the weather-resistant nano elastic paint according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) putting epoxy resin, modified glass flakes, nano titanium dioxide and organic solvent into a high-speed disperser and stirring them uniformly to obtain a mixture; (2) Put the curing agent into a high-speed disperser and continue stirring to obtain a weather-resistant nano elastic paint.

Citation Information

Patent Citations

  • Novel flaky reflective thermal insulation powder and preparation method thereof

    CN105694574A

  • Basalt flake anticorrosion paint

    CN106590356A

  • Titanium dioxide cladded hollow glass microsphere thermal insulation coating and preparation method thereof

    CN107841223A

  • Preparation method of epoxy heavy duty anticorrosion coating

    CN108129949A

  • Flame-retardant raw lacquer as well as preparation method and application thereof

    CN114933856A